Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Bing Liu; Jiao Qiao; Jinxiu Hu; Minghua Fan; Yanfang Zhao; Hong Su; Ziyang Wang; Qun Yu; Qiqi Ma; Yanmei Li; Zhimei Lv; Rong Wang (Molecular and Cellular Biochemistry, 2020)

SNP discovery in Mauremys reevesii and M. sinensis using restriction site-associated DNA sequence (RAD-seq) - Qiming Xie; Chaozhen Rong; Xilei Li; Nianyue Lai; Tiantian Chen; Qingqing Li; Shiping Su (Conservation Genetics Resources, 2020)

Habitat fragmentation changes top‐down and bottom‐up controls of food webs - Rong Wang; Xin Zhang; Yi‐Su Shi; Yuan‐Yuan Li; Jianguo Wu; Fangliang He; Xiao‐Yong Chen (Ecology, 2020)
Top‐down and bottom‐up controls regulate the structure and stability of ecosystems, but their relative roles in terrestrial systems have been debated. Here we studied a hydro‐inundated land‐bridge system in subtropical China and tested the relative importance of these two controls in determining the rodent‐mediated regeneration of a locally dominant tree species. Our results showed that both controls operated in terrestrial habitats and that their relative importance switched as habitat size changed. Habitat loss initially removed predators of rodents that released rodent populations and triggered massive seed predation (top‐down control), leading to reduced seedling establishment. A further reduction in habitat size led to decrease in rodent population that was supposed to increase seedling survival of the tree species, but the decline in habitat size deteriorated the abiotic environments (bottom‐up control) that severely prevented seedling recruitment. As the ongoing global land use change is creating increasing number of small‐sized forest fragments, our findings provide novel insights into the restoration of seriously fragmented forests.

Obtaining More Information about Precipitation Biases over East Asia from Hourly-Scale Evaluation of Model Simulation - Nina Li; Jian Li; Xinyao Rong; Haoming Chen; Yufei Xin; Jingzhi Su (Journal of Meteorological Research, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Expression of the kisspeptin/gonadotropin-releasing hormone (GnRH) system in the brain of female Chinese sucker (Myxocyprinus asiaticus) at the onset of puberty - Shiping Su; Qingqing Li; Xilei Li; Chaozhen Rong; Qiming Xie (Fish Physiology and Biochemistry, 2020)